(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
When it comes to mechanical characteristics, banana fibre is second to none, and it’s abundant in nature. Efficient cooling can extend the life of the engine and enhance its performance. In order to evaluate the relative heat dissipation capabilities of aluminium and copper radiator tubes, this project calls for the construction of a flow heat exchanger. We calculated heat transfer and total efficiency using the log mean temperature difference approach. The ANSYS software was also used for the thermal behaviour investigation. A cooling fan is important to this project’s simulation of real-time conditions for moving and idle variables (forced and free convection). Both theoretical and experimental investigations into cross-flow heat exchangers have yielded the following results: the heat transfer and overall heat transfer coefficients are determined by using the log mean temperature difference method, which is dependent on the inlet and outlet fluid temperatures as well as the effectiveness of the device. This finding demonstrates that heat transfer is linearly proportional to the mass flow rate of air and that its effectiveness is inversely proportional to the mass flow rate.